Notes on the genus Netelia, subgenus Parabates (Ichneumonidae, Tryphoninae), with description of a new species from Oriental Region - Pham, Nhi Thi; Chen, Hsuan-Pu; Konishi, Kazuhiko (Zootaxa, 2021)
The characters that define the subgenus Parabates of the genus Netelia are investigated. The shape of the basal apodeme of the aedeagus is considered to be a synapomorphy of this subgenus, suggesting the monophyly of Parabates. A new species, Netelia (Parabates) fusciapicalis n. sp. belonging to the ishiharai group is described from Taiwan, Vietnam and Laos. This is the sixth extant species of the subgenus, the first record of the genus Netelia from Vietnam and Laos, and the first record of the subgenus Parabates from Taiwan.